(untitled) (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2013)
Background: A lipoma in limbosanal region can be associated with myelomeningocele with tethered cord. Tethered cord means abnormally low conus medullaris with abnormally thick filum terminale attached to lower sacral region. Objective: The case was discussed because there is rare association between lipomyelomeningocele with tethering of cord, scolosis and clubfoot. The operation was done by S shaped transverse incision crossing over the middle of the lump. Excision of lipoma was done. Neural placode was identified and dethering of cord and repair of sac was done. Results: The muscle power after surgery was improved. There was no bladder disturbance and gait was intact. Conclusion: There was rare association of many congenital anomalies. Early diagnosis and surgery prevent future cord infarction and scoliosis, due to undue traction of cord. DOI: http://dx.doi.org/10.11566/cmoshmcj.v12i1.27 Chatt Maa Shi Hosp Med Coll J 2013; 12(1): 41-44